The Entrepreneurs' Acceptence Ability in Learning The Use of Digital Media - Miftahul Rozaq; Sri Hastjarjo; Yulius Slamet (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
In today's digital era, learning the use of digital media for entrepreneurs is mostly done by imitation through various role models on digital media such as content creators who display various content strategies for business development. However, success in learning through observation on digital media depends on the entrepreneurial receptivity ability to assess, interpret and apply the knowledge gained from the observed results. This study aims to investigate the acceptance of entrepreneurs in learning the use of digital media in an effort to develop their business. The research was conducted with a qualitative approach using a case study method on six novice entrepreneurs from micro, small and medium enterprises in Surakarta City, Indonesia. In-depth interviews were conducted from October 2020 – to March 2021. The results showed that three entrepreneurs in each use of digital media strategies were in a dominant acceptance position, two entrepreneurs were in a negotiating position, and one entrepreneur was in an oppositional position. Entrepreneurial receptions in the three acceptance positions show, among other things, in the dominant acceptance the entrepreneur makes a similar imitation, in the negotiated acceptance the entrepreneur carries out development, and in the oppositional acceptance the entrepreneur makes a new version. Keywords: case studies, entrepreneurship learning, reception analysis, SMEs. use of digital media strategies